2012
DOI: 10.1165/rcmb.2012-0011oc
|View full text |Cite
|
Sign up to set email alerts
|

CHRNA3/5, IREB2, and ADCY2 Are Associated with Severe Chronic Obstructive Pulmonary Disease in Poland

Abstract: We examined the association between single-nucleotide polymorphisms (SNPs) previously associated with chronic obstructive pulmonary disease (COPD) and/or lung function with COPD and COPD-related phenotypes in a novel cohort of patients with severe to very severe COPD. We examined 315 cases of COPD and 330 Caucasian control smokers from Poland. We included three SNPs previously associated with COPD: rs7671167 (FAM13A), rs13180 (IREB2), and rs8034191 (CHRNA 3/5), and four SNPs associated with lung function in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 36 publications
0
65
0
1
Order By: Relevance
“…33 Variants in the THSD4 locus have been found to be associated with lung function 34 and, in particular, lung function in severe COPD. 35 This study revealed differentially methylated sites annotated to COPD GWAS candidate genes and genes with previously identified links to lung disease and treatment response, as well as others in physical proximity with known GWAS susceptibility loci. These sites have strong support in this study.…”
Section: Discussionmentioning
confidence: 64%
“…33 Variants in the THSD4 locus have been found to be associated with lung function 34 and, in particular, lung function in severe COPD. 35 This study revealed differentially methylated sites annotated to COPD GWAS candidate genes and genes with previously identified links to lung disease and treatment response, as well as others in physical proximity with known GWAS susceptibility loci. These sites have strong support in this study.…”
Section: Discussionmentioning
confidence: 64%
“…2527 In prior reports, neither the connection between ADCY and the disorder nor the nature of the cAMP changes were clearly defined. Our findings, that ADCY5 mutations in FDFM in different protein domains increase intracellular cAMP in mutant ADCY5 -transfected cells in response to isoproterenol, an agonist of the β-adrenergic system through its receptor, are to our knowledge the first demonstration directly linking mutations in an ADCY and a human disease.…”
Section: Discussionmentioning
confidence: 97%
“…Development of AC2-selective inhibitors may overcome the difficulties to elucidate the (patho)physiologic functions of AC2 (Pinto et al, 2008;Erdorf et al, 2011;Kinast et al, 2012;Conley et al, 2013). ADCY2 polymorphisms may be related to neuropsychiatric (Mühleisen et al, 2014;Suarez-Rama et al, 2015) and pulmonary diseases (Hardin et al, 2012;Panasevich et al, 2013). Pharmacological studies point to a role of AC2 in the pathogenesis of Lesch-Nyhan disease, a neuropsychiatric disorder with severe self-injurious behavior (Kinast et al, 2012).…”
mentioning
confidence: 99%